HIGHLY PATTERNED PRIMARY SUCCESSION AFTER FLUVIAL DEPOSITION OF MINING WASTE - Nikolić, Nina (Bulletin of Natural Sciences Research, 2020)
This study examined early stages (3-5 years) of spontaneous primary vegetation succession on a model locality drastically altered by long term fluvial deposition of copper tailings in Eastern Serbia. In a large-scale survey, 115 samples of herbaceous vegetation (with a total of 75 species) were harvested from standardized 1m x 1m quadrates, and concomitant soil samples collected and their relevant physicochemical properties analysed. Primary succession depended on the establishment of five pioneer species (Rumex acetosella, Agrostis capillaris, Calamagrostis epigeios, Persicaria lapathifolia and  Chenopodium botrys). Unconstrained ordination showed very clear vegetation gradients, significantly correlated with the key soil constraints (from Cu excess to low pH and nutrient deficiency), while the distribution of the five edificatory pioneers showed high degree of dependence on the micro-level habitat conditions. This work demonstrates that in such a complex setup with severe abiotic filtering, sufficient sampling effort can reveal strong patterns in a process commonly considered very stochastic.
Keywords: Copper; Gradient analysis; Habitat Modeling; Primary Vegetation Succession